Evaluation of a New Chemiluminescent Immunoassay-Based Interferon-Gamma Release Assay for Detection of Latent Tuberculosis Infection - Keun Ju Kim; Seong-Eun Ryu; Ha-Na Lee; Seung-Hwan Oh; Chulhun L. Chang (Medicina, 2023)
Background and Objectives: This study aimed to evaluate the performance of a new chemiluminescent immunoassay-based tuberculosis (TB) interferon-gamma release assay (IGRA), AdvanSureI3 TB-IGRA (LG Chem Ltd., Seoul, Republic of Korea), for detecting latent tuberculosis infection in comparison with T-SPOT.TB (Oxford Immunotec, Oxford, UK). Materials and Methods: Between June 2021 and December 2021, 125 non-duplicate blood specimens were collected from adult volunteers; each subject received both tests concurrently. Total agreement and Cohen’s kappa coefficient (κ) were used to calculate concordance. The Jonckheere–Terpstra test was used to examine the correlation between interferon-gamma (IFN-γ) levels in AdvanSureI3 TB-IGRA and spot counts in T-SPOT.TB. Results: The IGRA findings of the two assays revealed 90.8% (95% confidence interval [CI] = 84.2–94.8) total agreement with κ of 0.740 (95% CI = 0.595–0.885), showing substantial agreement between the two tests. Additionally, the amount of IFN-γ in AdvanSureI3 TB-IGRA increased with the spot counts in T-SPOT.TB (p < 0.001). Conclusions: Our research revealed that the results of the AdvanSureI3 TB-IGRA were comparable to those of T-SPOT.TB.